PENGARUH DISIPLIN, KOMUNIKASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (BPKAD) PEMATANG REBA - Sri Rahayu Julianti; Mei Indrawati; Indra Presetyo (MAP (Jurnal Manajemen dan Administrasi Publik), 2018)
This study aims to describe discipline, communication, motivation and performance of employees in the Regional Financial and Asset Management Agency (BPKAD) in Pematang Reba. Furthermore, to know the influence of discipline, communication and motivation either partially or simultaneously to the performance of Employees of Financial Management and Regional Assets (BPKAD) in Pematang Reba. This research is an explanatory research with quantitative approach. The location of this research is in the Regional Financial and Asset Management Board (BPKAD) in Pematang Reba. The population in this research is all employees of Financial and Asset Management Agency (BPKAD) in Pematang Reba as many as 105 people. The technique of sampling in with the census sample technique that is all the population becomes the research sample, and the number of samples in this study is 104 people hereinafter called respondent. The result of data analysis shows that simultaneously organizational culture, commitment and work motivation have a significant effect to the performance of employees of Financial and Regional Asset Management Board (BPKAD) in Pematang Reba. Variables of discipline, communication, and motivation each have a significant effect on the performance of employees of the Financial and Regional Asset Management Board (BPKAD) in Pematang Reba. Keywords: discipline, communication, motivation and employee performance